Penanaman Nilai-Nilai Pendidikan Karakter di Madrasah Ibtida’iyah Darul Ulum Kediri - Ari Susetiyo; Suttrisno (Jurnal Riset Madrasah Ibtidaiyah, 2022)
This Study will discuss about character education, and character education in Madrasah Ibtida’iyah Darul Ulum Pohsarang. This type of research is qualitative research, using a qualitative description approach, which is used to describe the values of moral education in Madrasah Ibtida’iyah Darul Ulum, the results of this study showed that in Madrasah Darul Ulum Pohsarang has carried out habituation in the morning by shaking hands when entering, habituation shaking hands when entering the madrasah gate, this is done so that students are accustomed to respecting teachers, respecting people older than them. Carry out habituation Dhuha prayers, students have good morals by doing habituation Dhuha prayer every morning. Role models which are examples of teachers, educators as well as madrasah employees make examples of good manners by saying politely to students, as well as examples to employees. Integrating through scout extracurricular activities, in scout activities, it makes students to learn independently, learn to be responsible, learn to work hard, learn to appreciate the work of the efforts achieved, love the homeland, and care about the environment around.